Presence of a circumsporozoite-like protein in micronemes of blood-stage merozoites of malaria parasites. - Cochrane, A. H. (World Health Organization, 1990)
We demonstrate for the first time the presence of a circumsporozoite (CS)-like protein in invasive blood stages of malaria parasites. Immunogold electron microscopy using antisporozoite monoclonal antibodies localized these antigens in the micronemes of merozoites. Western immunoblot and two-dimensional gel electrophoresis of mature blood-stage extracts of Plasmodium falciparum, P. berghei, P. cynomolgi, and P. brasilianum identified polypeptides having the same apparent molecular mass and isoelectric points as the corresponding sporozoite (CS) proteins. The CS-like protein of merozoites is present in relatively minor amounts, compared to the CS protein of sporozoites. Mice with long-term P. berghei blood-induced infections develop antibodies which react with sporozoites.